2012
DOI: 10.1007/s10040-012-0840-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological characterization of Gold Valley: an investigation of precipitation recharge in an intermountain basin in the Death Valley region, California, USA

Abstract: Gold Valley is typical of intermountain basins in Death Valley National Park (DVNP), California (USA).Using water-balance calculations, a GIS-based analytical model has been developed to estimate precipitational infiltration rates from catchment-scale topographic data (elevation and slope). The calculations indicate that groundwater recharge mainly takes place at high elevations (>1,100m) during winter (average 1.78mm/yr). A resistivity survey suggests that groundwater accumulates in upstream compartmentalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Revil et al (2012) in their recent research had explained about the low-frequency electrical methods for subsurface characterization and monitoring in hydrogeology. Abdulaziz et al (2012) in their work demonstrated subsurface characterization and groundwater flow. Though multi electrode resistivity tomography technique is more expensive compared to traditional DC resistivity survey, the additional cost may be justified where the prospecting, exploration and demand for groundwater is relatively high especially in heterogeneous, rugged and different geological settings.…”
Section: Introductionmentioning
confidence: 98%
“…Revil et al (2012) in their recent research had explained about the low-frequency electrical methods for subsurface characterization and monitoring in hydrogeology. Abdulaziz et al (2012) in their work demonstrated subsurface characterization and groundwater flow. Though multi electrode resistivity tomography technique is more expensive compared to traditional DC resistivity survey, the additional cost may be justified where the prospecting, exploration and demand for groundwater is relatively high especially in heterogeneous, rugged and different geological settings.…”
Section: Introductionmentioning
confidence: 98%
“…The distribution and overall volume of water contained in these reservoirs are the least known primarily because of their high degree of heterogeneity and overall low productivity (Comte et al, 2012a). It is however acknowledged that most of groundwater flow and storage take place at a relatively shallow depth within the most weathered/fractured bedrock (Abdulaziz et al, 2012;Kumar et al, 2016). Such shallow depths of interest (tens of meters) make near-surface geophysical techniques suitable to characterize and understand weathered/fractured basement rock aquifers (Day-Lewis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%